Responsible Remembering and Forgetting in Younger and Older Adults. Issue 5 (20th October 2022) - Murphy, Dillon H.; Castel, Alan D.
ABSTRACT: Although older adults are often concerned about instances of forgetting, forgetting can be a useful feature of our memory system. Specifically, strategically forgetting less important information can benefit memory for goal-relevant information (i.e., responsible remembering and responsible forgetting). In two experiments, we presented younger and older adults with a list of words (either unrelated words or items to bring on a camping trip) with a cue indicating whether participants ("You") or their "Friend" was responsible for remembering each item. Results revealed that both younger and older adults engaged in responsible remembering and forgetting by better remembering items they were responsible for remembering, indicating a strategic utilization of their limited memory capacity. Additionally, regardless of age and the cue indicating who was responsible for remembering each item, participants used importance to guide the encoding and retrieval of information. Thus, people may be able to engage strategic cognitive mechanisms to maximize memory utility for important, goal-relevant information, and responsible forgetting can enhance memory utility in both younger and older adults by using importance to drive memory and reduce consequences for forgetting.